Lithium-aluminum-silicon cover plate glass and strengthening method thereof
Through multiple ion exchange and three-wheel gradient cooling treatment, the problem of increasing the compressive stress depth during the strengthening process of lithium-aluminum silicon glass is solved, and the impact strength is improved and the compressive stress distribution and safety is balanced, which is improved, and the mechanical properties and application prospects of the glass are improved.
Patent Information
- Application Number
- CN202411728097.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-07
AI Technical Summary
It is difficult for existing lithium-aluminum silicon glass to further increase the compressive stress depth during the strengthening process, resulting in limited mechanical properties. The stress data measured by the optical stress meter cannot accurately reflect the compressive stress and tensile stress state inside the glass, resulting in unstable strength and drop resistance.
The multi-ion exchange process is adopted, and the lithium-aluminum silicon glass is employed to carry out multiple ion exchange and three-wheel gradient cooling treatments by configuring different proportions of ion exchange molten salts of lithium nitrate, sodium nitrate and potassium nitrate, and the expansion coefficient and grain size of the glass are controlled, and the compressive stress depth and impact strength of the glass are improved.
The compressive stress depth of lithium-aluminum silicon glass has been improved, the impact strength is improved, and the effective balance between compressive stress distribution and safety is achieved, enhancing the application prospects of glass.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass production, and in particular relates to a lithium aluminum silicon cover glass and a strengthening method thereof. Background Art
[0002] Compared with traditional soda-lime-silica glass and high-aluminum glass, lithium aluminosilicate glass has the characteristics of dense network structure, high elastic modulus, relatively low Tg and suitable two-step chemical tempering. It is regarded as the third generation of high-strength glass substrate and has attracted much attention in recent years. The CS and DOL of lithium aluminosilicate glass after chemical tempering are extremely excellent, reaching 900MPa and above 300μm respectively, indicating that it has good strength, hardness and drop resistance. It can be used as cover glass for electronic devices such as mobile phones, computers and display screens. It is also an important glass substrate for aircraft windshields, high-speed rail windshields and special vehicle windows.
[0003] Chinese patent CN114031293A discloses lithium aluminosilicate glass and a preparation method thereof and strengthened lithium aluminosilicate glass and a preparation method thereof, which uses 50-100% sodium nitrate and 0-50% potassium nitrate for a first strengthening treatment at 400-450°C, and then uses 95-100% potassium nitrate and 0-5% sodium nitrate for a second strengthening treatment at 400-440°C, and finally obtains a lithium aluminosilicate glass with excellent anti-blue light effect, and also has high hardness, high light transmittance and scratch resistance and other properties.
[0004] Chinese patent CN112707639A discloses lithium aluminum silicate glass, tempered glass, preparation method thereof and electronic products. The lithium aluminum silicate glass comprises, by mass percentage, SiO2 50% to 64%, Al2O3 21% to 30%, Li2O 1.1% to 6%, Na2O 3% to 9%, P2O5 3.1% to 8%, B2O 30% to 5%, ZrO 20% to 3%, K2O 2.1% to 6%, MgO 0% to 2% and ZnO 0% to 1%, wherein 10% ≤ R2O ≤ 15%, and RO ≤ 2%. The lithium aluminum silicate glass can be tempered by a mixed salt of potassium nitrate and sodium nitrate in one step by adjusting the composition and proportion, so that the tempered glass has both good strength and drop resistance.
[0005] Existing lithium aluminosilicate glass obtains composite compressive stress with a surface high stress area and a deep compressive stress area through binary ion exchange of sodium-lithium and potassium-sodium ions. Under the same thickness, the compressive stress depth of lithium aluminosilicate glass is nearly 2-3 times higher than that of high aluminosilicate glass, which greatly improves the drop resistance of lithium aluminosilicate glass. However, the compressive stress range detected on both sides of lithium aluminosilicate glass is close to 40% of the glass thickness, and due to the existence of tensile stress, it is currently difficult to further increase the compressive stress depth through strengthening technology to improve the mechanical properties of strengthened glass.
[0006] In addition, the current state control of the composite compressive stress of lithium aluminosilicate glass is achieved through an optical stress meter, which obtains stress parameters such as CS, DOL-0, and CT through changes in refractive index and light scattering to characterize the stress state, and the CG factory uses this to control the stress state of the glass. However, experiments have found that the stress data measured by the current optical instrument cannot actually reflect the true state of compressive stress and tensile stress inside the glass, and the higher the CS and DOL-0 of lithium aluminosilicate glass, the better the strength. When CT is low, the strength of lithium aluminosilicate glass is not high; when CT is high, the drop resistance of lithium aluminosilicate glass is unstable. Therefore, the optimal distribution of compressive stress and the safety of compressive stress in the current lithium aluminosilicate glass cannot achieve an effective balance, resulting in the current lithium aluminosilicate glass having a loss of strength and drop resistance, which limits the current application of lithium aluminosilicate glass. Summary of the invention
[0007] In response to the above technical problems, the present invention provides a lithium aluminum silicon cover glass and a strengthening method thereof, which increases the compressive stress depth of the lithium aluminum silicon cover glass, thereby improving the impact strength and achieving an effective balance between the optimal distribution of compressive stress and safety.
[0008] In order to achieve the above object, the present invention provides a method for strengthening lithium aluminum silicon cover glass, comprising the following steps: (1) preparing a first ion exchange molten salt: mixing and melting lithium nitrate, sodium nitrate and potassium nitrate to obtain a first ion exchange molten salt; (2) placing the lithium aluminum silicon cover glass in an ion exchange molten salt for one ion exchange, cooling it naturally to room temperature, and then washing it with deionized water; (3) The cleaned glass is heated to 800-900°C at a rate of 1-5°C / min, then kept at that temperature for 60-120s, and then cooled to obtain strengthened glass; (4) placing the tempered glass in a second ion exchange molten salt for secondary ion exchange, cooling it naturally to room temperature, and then washing it with deionized water to obtain secondary exchange glass; (5) placing the secondary exchange glass in a third ion exchange molten salt for a third ion exchange, cooling it naturally to room temperature, and then washing and cooling it with deionized water to obtain a strengthened lithium aluminum silicon cover glass.
[0009] Preferably, the ion exchange molten salt in step (1) is composed of the following raw materials in percentage by mass: 40-60% lithium nitrate, 20-40% sodium nitrate and 10-25% potassium nitrate.
[0010] Preferably, the ion exchange conditions in step (2) are 290-330° C. for 30-120 seconds.
[0011] Preferably, the cooling treatment in step (3) is three rounds of gradient cooling treatment.
[0012] Further preferably, the three rounds of gradient cooling treatment include the following contents: The first round of cooling treatment: cooling to 650-750℃ at a rate of 18-25℃ / min; The second round of cooling treatment: cooling to 550-650℃ at a rate of 5-9℃ / min; The third round of cooling treatment: cooling to 30°C at a rate of 15-25°C / min.
[0013] Preferably, the second ion exchange molten salt in step (4) is composed of 40-100% sodium nitrate and 0-60% potassium nitrate in terms of mass percentage; and the secondary ion exchange condition is to keep warm at 390-450° C. for 90-240 min.
[0014] Preferably, the third ion exchange molten salt in step (5) is composed of 80-100% potassium nitrate and 0-20% sodium nitrate in terms of mass percentage.
[0015] Preferably, the tertiary ion exchange conditions in step (5) are to keep the temperature at 380-420°C for 60-180 min; the cooling is to keep the temperature in an annealing furnace at 360°C for 10-15 min, and then cool down to room temperature with the furnace.
[0016] The present invention also provides a lithium aluminum silicon cover glass, which is obtained by strengthening according to the above-mentioned strengthening method; the lithium aluminum silicon cover glass is composed of the following raw materials in mass percentage: 56-69% SiO2, 10-25% Al2O3, 0.1-7% Na2O, 0.1-5% K2O, 0.1-12% CaO, 0.1-7% MgO, 0.5-4% P2O5, 1-5.5% B2O3, and 0.2-5% ZrO2.
[0017] Preferably, the raw materials of the lithium aluminum silicon cover glass satisfy 0.2≤(MgO+CaO) / (P2O5+ZrO2)≤9.3.
[0018] The beneficial effects of the present invention are: 1. A first ion exchange molten salt is prepared with a large amount of lithium nitrate, potassium nitrate and sodium nitrate to perform an ion exchange on the lithium aluminum silicate glass. The lithium nitrate in the first ion exchange molten salt has a faster ion exchange reaction rate with the glass, and the lithium ions quickly exchange the sodium and potassium ions in the glass, thereby increasing the tensile stress of the lithium aluminum silicate glass. At the same time, the temperature and time of the first ion exchange are controlled to control the sodium and potassium ions exchanged by the lithium ions, thereby avoiding a rapid increase in the tensile stress of the glass, resulting in a loose glass structure, and more microcracks in the glass, resulting in a decrease in the strength of the glass. In addition, the lithium nitrate content in the first ion exchange molten salt is controlled to control the lithium ion exchange rate of the molten salt.
[0019] 2. Using three rounds of gradient cooling to cool and strengthen the single exchange glass can make the lithium ions enriched on the glass surface form tiny β-eucryptite or β-spodumene or petalite grains. The glass crystal size is small, 18-35nm, and a low expansion coefficient crystal phase is obtained on the glass surface. After cooling, compressive stress is generated to improve the strength of the glass, and the transmittance of the glass can be guaranteed. At the same time, multiple rounds of gradient cooling treatment can also make the internal structure of the glass gradually adapt to the rapid change of internal residual stress in the cooling process, which has a strong impact on its main structure, ensuring that the glass will not crack or warp in the subsequent strengthening process. The second stage cooling rate is controlled at 5-9℃ / min, which can prevent the cooling rate from being too fast, which will cause a large impact on the glass structure, and the glass will have a low impact strength after subsequent chemical strengthening, and avoid the cooling rate from being too slow, which will cause the crystal size to be too large and the transmittance to be low, resulting in a small compressive stress caused by the expansion coefficient difference, and also resulting in a low impact resistance of the glass.
[0020] 3. After three ion exchanges, the lithium aluminum silicon cover glass prepared by the present invention can maintain an average expansion coefficient between 0.085% and 0.21%, a ball drop height of more than 180 cm, and a 180-mesh sandpaper drop height of more than 250 cm. The strength is significantly improved, and an effective balance between compressive stress distribution and compressive stress safety can be achieved, thereby having a wider application prospect. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further explained below in conjunction with specific embodiments. It is worth noting that the following embodiments are only preferred embodiments of the present invention and should not be construed as limiting the present invention. The protection scope of the present invention shall be subject to the contents recorded in the claims. Any modification or replacement made by a person skilled in the art to the technical solution of the present invention without creative work shall fall within the protection scope of the present invention.
[0022] The performance parameter detection methods of the following embodiments and comparative examples are as follows: Average expansion rate A: Take 10-20 pieces of lithium aluminum silicate glass to test their length and width, then perform ion exchange and other tempering steps on them, and then test their length and width again. Length expansion rate = (length after tempering - length before tempering) / length before tempering; width expansion rate = (width after tempering - width before tempering) / width before tempering, average expansion rate A = (length expansion rate + width expansion rate) / 2; Sandpaper drop height: Use a drop test machine, simulate a mobile phone model weighing 200g, place 180-mesh or 80-mesh silicon carbide sandpaper on the ground, face down at a free fall speed, starting at 40cm, and increase by 10cm each time until the glass breaks (if cracks appear, it is broken). The height at which the glass breaks is the drop height of the 180-mesh sandpaper or the 80-mesh sandpaper. Ball drop height: Tested in accordance with GB / T 20138-2006; The stress testers FSM6000UV and SLP2000 manufactured by Japan Orihara were used to detect the glass surface stress value CS-K, the compressive stress value CS-Na at a depth of 30 μm, the maximum stress layer depth Dol-K of potassium ions, and the maximum stress layer depth Dol-Na of stress values.
[0023] Precursor visible light transmittance: Referring to the standard ISO13468-1:1996, the transmittance of the lithium aluminum silicon cover glass prepared by molding and annealing at a wavelength of 420nm was tested using an infrared spectrophotometer: Visible light transmittance after surface crystallization: The transmittance of the crystallized glass at a wavelength of 420nm was tested using an infrared spectrophotometer after three rounds of gradient cooling: Main crystal phase: The crystal phase of the glass crystallized after three rounds of gradient cooling was tested by X-ray diffraction (XRD), with a scanning range of 0-180° and a step speed of 2° / min; Average grain size: The grain size of the crystallized glass after three rounds of gradient cooling was tested by scanning electron microscope; 4PB: The equipment is a four-point bending tester. Before the experiment, confirm that the appearance of the sample is OK. The sample size is 156*72*0.7mm. The strengthening parameters meet the requirements. Set the span and pressing speed according to the conditions. Press down with a cylindrical pressure rod until the cover plate breaks. Record the limit force value when the sample breaks. The upper span of the bending fixture is 20mm, the lower span is 40mm, the pressure rod is a ¢6mm steel rod, and the bending speed is 10mm / min.
[0024] Examples 1-4, Comparative Examples 1-2 (1) SiO2, Al2O3, Na2O, K2O, CaO, MgO, P2O5, B2O3 and ZrO2 are sequentially mixed, melted, homogenized, formed and annealed to prepare lithium aluminum silicon cover glass; the raw material ratio is shown in Table 1; (2) preparing a first ion exchange molten salt: mixing and melting 40% lithium nitrate, 40% sodium nitrate and 20% potassium nitrate according to mass percentage to obtain a first ion exchange molten salt; (3) placing the lithium aluminum silicon cover glass in the first ion exchange molten salt, keeping it at 300°C for 60 seconds, removing and cleaning the remaining molten salt on the surface, cooling it naturally to room temperature, and then washing it with 50°C deionized water to obtain a primary exchange glass; (4) The primary exchange glass is placed in a muffle furnace, heated to 800°C at a rate of 3°C / min, then kept at this temperature for 120s for crystallization, and then subjected to three rounds of gradient cooling to obtain the strengthened glass, as follows: S1: Cool down to 650℃ at a rate of 18℃ / min; S2: Cool down to 550°C at a rate of 8°C / min; S3: Cool down to 30°C at a rate of 15°C / min; (5) placing the strengthened glass in a second ion exchange molten salt, performing secondary ion exchange at 400° C. for 200 minutes, removing and cleaning the remaining molten salt on the surface, cooling naturally to room temperature, and then washing with deionized water at 50° C. to obtain a secondary exchange glass, wherein the second ion exchange molten salt is composed of 40% sodium nitrate and 60% potassium nitrate by mass percentage; (6) The secondary exchange glass is placed in a third ion exchange molten salt, and a third ion exchange is performed at 410°C for 110 minutes. The remaining molten salt on the surface is removed and cleaned, and the glass is naturally cooled to room temperature. The glass is then washed with deionized water at 50°C and transferred to an annealing furnace at 360°C. The glass is kept warm for 10 minutes and then cooled to room temperature with the furnace to prepare a strengthened lithium aluminum silicon cover glass. The third ion exchange molten salt is composed of 80% potassium nitrate and 20% sodium nitrate by mass.
[0025] Table 1 Effect of raw material ratio of lithium aluminum silicon cover glass on performance
[0026] The results are shown in Table 1: (MgO+CaO) / (P2O5+ZrO2) meets 0.2-9.3, which can make the glass surface crystallize, the average grain size is 18-35nm, and the glass transmittance will not decrease significantly after crystallization, and the transmittance is ≥91.2%.
[0027] Examples 5-8, Comparative Examples 3-4 (1) preparing lithium aluminum silicon cover glass according to the formula of Example 1; (2) preparing a first ion exchange molten salt: mixing and melting lithium nitrate, sodium nitrate and potassium nitrate to obtain a first ion exchange molten salt, wherein the formula of the first ion exchange molten salt is shown in Table 2; (3) placing the lithium aluminum silicon cover glass in a first ion exchange molten salt, heat-insulating and cleaning, to obtain a primary exchange glass, wherein the heat-insulating conditions are shown in Table 2; (4)-(6): As in Example 1, a strengthened lithium aluminum silicon cover glass is prepared.
[0028] Table 2 Effects of the first ion exchange molten salt and insulation conditions on glass properties
[0029] The results are shown in Table 2: lithium nitrate exchanges potassium and sodium ions in the glass to enrich potassium ions on the glass surface, and then controls the crystallization and three-stage cooling process to make the glass surface crystallize, and the grain size is controlled to be 22-35nm, which can ensure that the glass transmittance is greater than 91%. However, the exchange reaction rate of lithium nitrate and glass ions is relatively fast, and lithium ions exchange more sodium and potassium ions in the glass, which will cause the tensile stress of the glass to increase rapidly, resulting in a loose glass structure, and more microcracks will appear in the glass, causing the glass strength to decrease. It is necessary to control the exchange rate of molten salt lithium ions. If the mass fraction of lithium nitrate is greater than 60%, the exchange reaction rate of lithium nitrate and glass ions is relatively fast, and the crystal size after crystallization on the glass surface is larger, the transmittance is lower, and it is easy to break (Comparative Example 3); if the mass fraction of lithium nitrate is less than 40%, the exchange reaction rate of lithium nitrate and glass ions is relatively slow, the lithium ions on the glass surface are less enriched, and the glass cannot be crystallized on the surface (Comparative Example 3), and the glass strength is relatively low.
[0030] Examples 9-13, Comparative Examples 5-14 (1) preparing lithium aluminum silicon cover glass according to the formula of Example 1; (2) preparing a first ion exchange molten salt according to Example 7 and performing a first ion exchange to obtain a primary exchange glass; (3) The once exchanged glass was transferred to a crystallization furnace for crystallization, and then subjected to three rounds of gradient cooling to 30°C to obtain a strengthened glass. The crystallization conditions and the three rounds of gradient cooling conditions are detailed in Table 3. (4) placing the strengthened glass in a second ion exchange molten salt, performing secondary ion exchange at 400° C. for 200 minutes, removing and cleaning the remaining molten salt on the surface, and then washing with deionized water to obtain a secondary exchange glass, wherein the second ion exchange molten salt is composed of 40% sodium nitrate and 60% potassium nitrate by mass percentage; (5) The secondary exchange glass is placed in a third ion exchange molten salt, and after a third ion exchange at 410°C for 110 min, the remaining molten salt on the surface is removed and cleaned, and then the glass is washed with deionized water and transferred to an annealing furnace at 360°C. After being kept warm for 10 min, the glass is cooled to room temperature along with the furnace to prepare a strengthened lithium aluminum silicon cover glass.
[0031] Table 3 Crystallization and cooling conditions
[0032] Table 3 Effects of crystallization and cooling conditions on glass properties
[0033] The results are shown in Table 3: Through crystallization and three rounds of gradient cooling treatment, the lithium ions enriched on the surface of the glass can form tiny β-eucryptite or β-spodumene or petalite grains, the glass crystal size is small 22-35nm, and a low expansion coefficient crystal phase is obtained on the glass surface. After cooling, compressive stress is generated to improve the strength of the glass, and the transmittance of the glass can be guaranteed; at the same time, multiple rounds of gradient cooling treatment can also make the internal structure of the glass gradually adapt to the rapid change of internal residual stress in the cooling process, which has a strong impact on its main structure, ensuring that the glass will not crack or warp in the subsequent strengthening process. Too fast cooling rate will cause greater impact on the glass structure, and the impact strength of the glass will be lower after subsequent chemical strengthening; too slow cooling rate will cause the crystal size to be too large, the transmittance is low, and the compressive stress caused by the difference in expansion coefficient is small, which will also lead to lower impact resistance of the glass.
[0034] Examples 14-23, Comparative Examples 17-19 (1) preparing lithium aluminum silicon cover glass according to the formula of Example 1; (2) preparing a first ion exchange molten salt according to Example 7 and performing a first ion exchange to obtain a primary exchange glass; (3) performing crystallization and three rounds of gradient cooling according to the conditions of Example 11 to obtain strengthened glass; (4) placing the strengthened glass in a second ion exchange molten salt for secondary ion exchange, removing and cleaning the remaining molten salt on the surface, and then washing with deionized water to obtain a secondary exchange glass, wherein the formula of the second ion exchange molten salt and the conditions of the secondary ion exchange are shown in Table 4; (5) The secondary exchange glass was placed in a third ion exchange molten salt for a third ion exchange, and then the remaining molten salt on the surface was removed and cleaned. The glass was then washed with deionized water and transferred to an annealing furnace at 360°C. After being kept warm for 10 minutes, the glass was cooled to room temperature with the furnace to prepare a strengthened lithium aluminum silicon cover glass. The formula of the third ion exchange molten salt and the conditions of the third ion exchange are shown in Table 4.
[0035] Table 4 Formulas and conditions for secondary and tertiary ion exchange
[0036] Table 5 Effects of secondary and tertiary ion exchange on glass properties
[0037] Table 6 Effects of secondary and tertiary ion exchange on glass properties
[0038] It can be seen from Table 4-6 that during the second strengthening, sodium ions in the salt solution are used to exchange lithium ions in the glass, which is the main factor to increase stress CS-Na and DOL-Na. During the third strengthening, potassium ions in the salt solution are used to replace sodium ions in the glass, which is the main factor to increase stress CS-K and DOL-K, which can greatly shorten the time of glass strengthening. The three-time strengthening process has a good effect on improving the strength of lithium aluminum silicon glass by controlling the temperature and time of the glass in the salt solution, and the performance of the glass is stable after strengthening.
[0039] Comparative Example 20 (1) preparing lithium aluminum silicon cover glass according to the formula of Example 1; (2) The first ion exchange molten salt was prepared according to Example 7, and the first ion exchange was performed. After the molten salt remaining on the surface was removed and cleaned, the molten salt was naturally cooled to room temperature and then washed with deionized water at 50° C. to obtain a primary exchange glass; (3) placing the primary exchange glass in a second ion exchange molten salt, performing secondary ion exchange, removing and cleaning the remaining molten salt on the surface, cooling naturally to room temperature, and then washing with deionized water at 50° C. to obtain a secondary exchange glass, wherein the formula of the second ion exchange molten salt and the secondary ion exchange conditions are the same as those in Example 23; (4) The secondary exchange glass is placed in a third ion exchange molten salt, and after three ion exchanges, the remaining molten salt on the surface is removed and cleaned, and the glass is naturally cooled to room temperature, and then washed with 50°C deionized water and transferred to an annealing furnace at 360°C. After being kept warm for 10 minutes, the glass is cooled to room temperature along with the furnace to prepare a strengthened lithium aluminum silicon cover glass; wherein the third ion exchange molten salt formula and the three ion exchange conditions are the same as those in Example 23.
[0040] Comparative Example 21 (1) preparing lithium aluminum silicon cover glass according to the formula of Example 1; (2) The first ion exchange molten salt was prepared according to Example 7, and the first ion exchange was performed. After the molten salt remaining on the surface was removed and cleaned, the molten salt was naturally cooled to room temperature and then washed with deionized water at 50° C. to obtain a primary exchange glass; (3) Crystallization and three rounds of gradient cooling are performed according to the conditions of Example 11 to directly prepare the strengthened lithium aluminum silicon cover glass.
[0041] Comparative Example 22 (1) preparing lithium aluminum silicon cover glass according to the formula of Example 1; (2) placing the lithium aluminum silicate glass in a second ion exchange molten salt, performing secondary ion exchange, removing and cleaning the remaining molten salt on the surface, cooling naturally to room temperature, and then washing with 50° C. deionized water to obtain a secondary exchange glass, wherein the second ion exchange molten salt formula and ion exchange conditions are the same as those in Example 23; (3) The secondary exchange glass is placed in a third ion exchange molten salt, and after another ion exchange, the remaining molten salt on the surface is removed and cleaned, and the glass is naturally cooled to room temperature, and then washed with 50°C deionized water and transferred to an annealing furnace at 360°C. After being kept warm for 10 minutes, the glass is cooled to room temperature along with the furnace to prepare a strengthened lithium aluminum silicon cover glass; wherein the third ion exchange molten salt formula and the tertiary ion exchange conditions are the same as those in Example 23.
[0042] Comparative Example 23 (1) preparing lithium aluminum silicon cover glass according to the formula of Example 1; (2) The first ion exchange molten salt was prepared according to Example 7, and the first ion exchange was performed. After the molten salt remaining on the surface was removed and cleaned, the molten salt was naturally cooled to room temperature and then washed with deionized water at 50° C. to obtain a primary exchange glass; (3) performing crystallization and three rounds of gradient cooling according to the conditions of Example 11 to obtain strengthened glass; (4) The strengthened glass is placed in a second ion exchange molten salt, and after a secondary ion exchange, the remaining molten salt on the surface is removed and cleaned, and then the glass is washed with deionized water and transferred to an annealing furnace at 360° C., and the temperature is kept at 360° C. for 10 minutes and then cooled to room temperature with the furnace to prepare a strengthened lithium aluminum silicon cover glass; wherein the formula of the second ion exchange molten salt and the secondary ion exchange conditions are the same as those in Example 23.
[0043] Comparative Example 24 (1) preparing lithium aluminum silicon cover glass according to the formula of Example 1; (2) preparing the first ion exchange molten salt according to Example 7 and performing the first ion exchange, removing and cleaning the remaining molten salt on the surface, and then washing with deionized water to obtain a primary exchange glass; (3) performing crystallization and three rounds of gradient cooling according to the conditions of Example 11 to obtain strengthened glass; (4) The strengthened glass is placed in a third ion exchange molten salt, and after performing ion exchange again, the remaining molten salt on the surface is removed and cleaned, and then the glass is washed with deionized water and transferred to an annealing furnace at 360° C., and the temperature is kept at 360° C. for 10 minutes and then cooled to room temperature with the furnace to prepare a strengthened lithium aluminum silicon cover glass; wherein the formula of the third ion exchange molten salt and the conditions for the second ion exchange are the same as those in Example 23.
[0044] Results: The glasses prepared in Example 23 and Comparative Examples 20-24 were tested for performance. The results are shown in Table 7: Table 7 Effect of process on glass properties
[0045] The results can be seen from Table 7: Comparative Example 20 has no crystallization process, which will cause the glass tempering expansion rate to decrease, and there will be no grains on the glass surface to weaken crack expansion, which will reduce the glass strength; Comparative Example 21 has no second and third tempering processes, which will cause the glass tempering expansion rate to decrease, the glass surface stress is relatively low, the ability to resist crack expansion is weakened, and the glass strength is reduced; Comparative Example 22 has no first tempering process and crystallization process, which will cause the glass tempering expansion rate to decrease, and there will be no grains on the glass surface to weaken crack expansion, and no lithium ions enter the glass, and lithium-sodium ion exchange cannot occur, the depth of the stress layer on the glass surface is relatively low, and the ability to resist crack expansion is weakened, which will reduce the glass strength; Comparative Example 23 has no third tempering process, which will cause the glass tempering expansion rate to decrease, the glass surface stress is relatively low, the ability to resist crack expansion is weakened, and the glass strength is reduced; Comparative Example 24 has no second tempering process, which will cause the glass tempering expansion rate to decrease, the depth of the stress layer on the glass surface is relatively low, the ability to resist crack expansion is weakened, and the glass strength is reduced.
Claims
1. A method for strengthening lithium aluminum silicon cover glass, characterized in that: The steps include: (1) preparing a first ion exchange molten salt: mixing and melting lithium nitrate, sodium nitrate and potassium nitrate to obtain a first ion exchange molten salt; (2) placing the lithium aluminum silicon cover glass in an ion exchange molten salt for a first ion exchange and then cleaning; (3) The cleaned glass is placed at 800-900°C for 60-120 seconds, and then cooled to obtain strengthened glass; (4) placing the strengthened glass in a second ion exchange molten salt for secondary ion exchange, and washing to obtain secondary exchange glass; (5) placing the secondary exchange glass in a third ion exchange molten salt for a third ion exchange, cleaning and cooling the glass to obtain a strengthened lithium aluminum silicon cover glass.
2. The method for strengthening lithium aluminum silicon cover glass according to claim 1, characterized in that: The ion exchange molten salt in step (1) is composed of the following raw materials in percentage by mass: 40-60% lithium nitrate, 20-40% sodium nitrate and 10-25% potassium nitrate.
3. The method for strengthening lithium aluminum silicon cover glass according to claim 1, characterized in that: The ion exchange conditions in step (2) are 290-330° C. for 30-120 seconds.
4. The method for strengthening lithium aluminum silicon cover glass according to claim 1, characterized in that: The cooling treatment in step (3) is a three-round gradient cooling treatment.
5. The method for strengthening lithium aluminum silicon cover glass according to claim 4, characterized in that: The three rounds of gradient cooling treatment include the following: The first round of cooling treatment: cooling to 650-750℃ at a rate of 18-25℃ / min; The second round of cooling treatment: cooling to 550-650℃ at a rate of 5-9℃ / min; The third round of cooling treatment: cooling to 30°C at a rate of 15-25°C / min.
6. The method for strengthening lithium aluminum silicon cover glass according to claim 1, characterized in that: The second ion exchange molten salt in step (4) is composed of 40-100% sodium nitrate and 0-60% potassium nitrate in terms of mass percentage; the secondary ion exchange condition is to keep warm at 390-450° C. for 90-240 min.
7. The method for strengthening lithium aluminum silicon cover glass according to claim 1, characterized in that: The third ion exchange molten salt in step (5) is composed of 80-100% potassium nitrate and 0-20% sodium nitrate in terms of mass percentage.
8. The method for strengthening lithium aluminum silicon cover glass according to claim 1, characterized in that: The three ion exchange conditions in step (5) are to keep the temperature at 380-420°C for 60-180 minutes; the cooling is to keep the temperature in an annealing furnace at 360°C for 10-15 minutes, and then cool down to room temperature with the furnace.
9. A lithium aluminum silicon cover glass strengthened by the strengthening method according to any one of claims 1 to 8, characterized in that: The lithium aluminum silicon cover glass is composed of the following raw materials in percentage by mass: 56-69% SiO2, 10-25% Al2O3, 0.1-7% Na2O, 0.1-5% K2O, 0.1-12% CaO, 0.1-7% MgO, 0.5-4% P2O5, 1-5.5% B2O3, and 0.2-5% ZrO2.
10. The lithium aluminum silicon cover glass according to claim 9, characterized in that: The raw materials of the lithium aluminum silicon cover glass satisfy 0.2≤(MgO+CaO) / (P2O5+ZrO2)≤9.3.
Citation Information
Patent Citations
Lithium aluminosilicate glass, tempered glass and preparation method thereof, and electronic product
CN112707639A
Lithium-aluminum-silicon glass and preparation method thereof, and reinforced lithium-aluminum-silicon glass and preparation method thereof
CN114031293A
Chemical strengthening method of glass and glass prepared by chemical strengthening method
CN113816618A
Chemically strengthened aluminoborosilicate glasses
CN116903246A
Glass body having a semicrystalline surface layer and method of making it
US3253975A